2009
DOI: 10.1007/s00705-009-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative correlation between viral load and HBsAg levels in chronic HBV-infected patients

Abstract: The objective of this study is to reveal the relationship between viral load (as HBV DNA) and HBsAg levels. Ninety-two chronically HBV-infected patients were included in the study. The patients were divided in two different groups: the cirrhotic group (n = 32) and the non-cirrhotic group (n = 60). The correlation between study groups was also examined with regard to HBeAg status. Hepatitis B viral markers (HBsAg, HBeAg, Anti-HBs, anti-HBc and anti-HBe) and HBV viral load of the patients were measured. A signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…HBsAg and HBeAg are both accepted as the indicators of viral replication and a positive correlation is expected in fact. In the literature, there are studies that revealed positive correlation as well as many studies demonstrating negative correlation (5,6,8,14). We conclude that a negative correlation was detected in our study due to several different scenarios.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…HBsAg and HBeAg are both accepted as the indicators of viral replication and a positive correlation is expected in fact. In the literature, there are studies that revealed positive correlation as well as many studies demonstrating negative correlation (5,6,8,14). We conclude that a negative correlation was detected in our study due to several different scenarios.…”
Section: Discussionsupporting
confidence: 60%
“…Hepadnaviridae family members produce a large amount of viral envelope protein (HBsAg). The S protein is found both in intact viral particles and subviral particles which also contain M and L protein but not HBV DNA (5).These proteins are noninfectious but they are immunogenic (3). Both HBsAg and hepatitis B e antigen (HBeAg) represent viral replication and activation is suspected when an increase is detected in these markers.…”
Section: Introductionmentioning
confidence: 99%
“…Ozaras et al (2008) suggested that the HBsAg level was correlated with HBV DNA, and that it could replace HBV DNA to monitor the efficacy of pegylated interferon in the presence or absence of lamivudine marker. On the other hand, Ozdil et al (2009) reported a negative correlation between HBV DNA and HBsAg in non-cirrhotic chronic HBV-infected patients, whereas Kuhns et al (2004) found no correlation between HBsAg and HBV DNA in 200 blood samples. This could be attributed to various factors: 1) differences in the sensitivity of the HBV DNA detection protocol; most previous studies set a lower limit of detection as 103 copies/mL (not 1.16 x 10 2 copies/mL); 2) antiviral treatment (that some of the patients were subjected to) can induce mutations in the HBsAg sequence; viral variants appear as a result of endogenous (host immunity) and/or exogenous (immune-prophylaxis and antiviral therapy) factors (Locarnini and Zoulim, 2010); and 3) the high spontaneous error rate in the reverse transcriptase induces mutations in the virus, such as the preS/S variants (Pollicino et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…One explanation for this is that HBsAg levels are negatively correlated with viral load owing to a partial immunity that develops against HBV (Ozdil et al, 2009). The results indicate that serum HBV DNA and HBeAg as well as HBsAg level are in correlation with the detectable semen viral load and may have a predictive value for HBV DNA present in semen in men with HBV infection.…”
Section: Discussionmentioning
confidence: 61%